Efektivitas Penerapan Model Kooperatif Tipe Example Non Example dalam Pembelajaran Matematika Siswa Kelas VII SMP - Thamrin, Yusrianah; Rusli; Bernard (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2018)
This research aims to determine the effectiveness of implementing Example Non Example type of cooperative model in students’ mathematics learning of grade VII SMP by clicking refer to the three criteria of effectiveness of learning, i.e students’ learning achievement, students’ activities and responses. The data analysis technique that is used is the technique of descriptive and inferential statistical analysis. The results analysis of this research are: 1) the average percentage of students who is taught by Example Non Example type of cooperative model greater than 75 (KKM), (2) the average value of normalized gain greater than 0,3 (medium category), (3) there is a significant difference in mathematics learning achievement before and after the use of the Example Non Example type of cooperative model, (4) the average percentage of students’ activities is 88,97%, (5) the average percentage of students who gave positive responses to the implementation of learning is 94,83%, (6) The average of learning accomplishment using Example Non Example type of cooperative model is 3.82 (very well done). From these results it can be concluded that learning with Example Non Example type of cooperative model is effective to be used in students’ mathematics learning of grade VII in one of school in.